Advances in Multitarget Therapeutic Approaches for Immune-Mediated Glomerular Diseases - Luminita Voroneanu; Andreea Covic; Vladimir Tesar; Mehmet Kanbay; Adrian Covic (Life)
Glomerulonephritis (GN) encompasses a diverse group of immune-mediated diseases that damage the glomerular component of the nephron. While kidney biopsy remains the gold standard for diagnosis, it often fails to provide adequate insight into the underlying etiology of GN. Current classification systems have limited our understanding of the disease’s pathophysiology and hinder the development of targeted therapies. Immunosuppressive treatments, such as glucocorticoids, calcineurin inhibitors, cyclophosphamide, and rituximab, remain the mainstay of therapy, though many patients fail to achieve remission or experience significant adverse effects. Moreover, the complex and multifactorial nature of GN pathogenesis calls for more refined therapeutic approaches. In recent years, multitarget therapies—combining different immunosuppressive agents targeting distinct immune pathways—have emerged as promising alternatives. Evidence suggests that multitarget therapy may offer superior outcomes compared to standard treatments. Despite early success, further studies are needed to optimize these regimens, reduce toxicity, and extend benefits to a broader range of GN patients. The development of personalized, biomarker-driven treatments, potentially leveraging innovative drug delivery systems and targeted biologics, holds promise for transforming GN care in the future.